"Immigration Problems Facing the European Union from the Perspective of UN Human Rights Council Mechanisms" - Hernandez-Połczyńska, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The scale of immigration problems in Europe today is well-known and broadly dis-cussed. The article identifies how this issue is reflected in two Human Rights Council mechanisms: Special Procedures and the Universal Periodic Review. The Special Rap-porteur on the human rights of migrants, François Crépeau, undertook a regional study on the management of the external borders of the European Union and its impact on the human rights of migrants. The analysis of the annual and country visits’ reports allows the main immigration problems facing the EU countries and threats for the protection of human rights to be identified. The recommendations made by the Special Rapporteur are confronted with those taken up in the UPR process. Special attention is given to the EU countries’ position on the problem of immigrants. Their reluctance to raise this issue in the UPR weakens the credibility of EU Member States and puts the objectivity of the mechanism into question.